A SRM for a PV Powered Water Pumping System Based on a Multilevel Converter and DC/DC Dual Output Converter - Foito, Daniel José Medronho (2022)
Trabalho apresentado em 7th International Conference on Smart and Sustainable Technologies - Splitech 2022, 5-8 julho 2022, Bol, Croatia